The IRAS 08589-4714 star-forming region - Saldaño, Hugo Pablo (2017)
We present an analysis of the IRAS 08589-4714 star-forming region. Thisregion harbors candidate young stellar objects identified in the WISEand Herschel images using color index criteria and spectral energydistributions (SEDs). The SEDs of some of the infrared sources and the70 microns radial intensity profile of the brightest source (IRS 1) aremodeled from Herschel fluxes using the one-dimensional radiativetransfer DUSTY code. For these objects, we estimate the envelope masses,sizes, densities, and luminosities which suggest that they are veryyoung, massive and luminous objects at early stages of the formationprocess. Color-color diagrams in the bands of WISE and 2MASS are used toidentify potential young objects in the region. Those identified in thebands of WISE would be contaminated by the emission of PAHs. We use theemission distribution in the infrared at 70 and 160 microns, to estimatethe dust temperature gradient. This suggests that the nearby massivestar-forming region RCW 38, located ~ 10 pc of the IRAS source positionmay be contributing to the photodissociation of the molecular gas and tothe heating of the interstellar dust in the environs of the IRAS source.